The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1002/car.2380040303
|View full text |Cite
|
Sign up to set email alerts
|

Family participation in child protection

Abstract: The paper summarizes a Department of Health funded research study of the extent to which parents and children were involved in the child protection work of seven English social services departments. The child protection process and the social work practice with a cohort of 220 consecutive cases is described for the period before the initial conference and the 6 months following it. The authors draw on interview data from parents, young people and social workers and on social work records to assess whether the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 1 publication
0
28
0
Order By: Relevance
“…They further suggest that the treatment a family receives is likely to determine the extent to which the family will co-operate with the agencies, and that the quality of the families' experience may well be an influential factor in the ability of agencies to adequately monitor the well being of vulnerable children. Thoburn, Lewis and Shemmings (1995), in their extensive study of social work practice found that half the parents in child protection cases thought that they were helped or supported by their social worker. It was rare for family members to be involved in decisions about registration, protection plans and help offered, although more parents (about two fifths) were informed or consulted.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They further suggest that the treatment a family receives is likely to determine the extent to which the family will co-operate with the agencies, and that the quality of the families' experience may well be an influential factor in the ability of agencies to adequately monitor the well being of vulnerable children. Thoburn, Lewis and Shemmings (1995), in their extensive study of social work practice found that half the parents in child protection cases thought that they were helped or supported by their social worker. It was rare for family members to be involved in decisions about registration, protection plans and help offered, although more parents (about two fifths) were informed or consulted.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies focusing on ethnicity rather than child protection (Thoburn et al (1995); Thoburn, Chand and Proctor (2005); Quereshi et al (2000)) have found that black and ethnic minority families have generally coped no worse than white families; deprivation and income levels and standards of housing tend to be more powerful variables than ethnicity. However, there is agreement that families new to the UK found child protection systems confusing and anxiety provoking.…”
Section: Exploring the Experiences Of Parents And Carers Whose Childrmentioning
confidence: 99%
“…Codes were developed inductively working from the data (Braun & Clarke 2006). However, inevitably researchers drew upon background knowledge of existing typologies of participation (Arnstein 1969;Hart 1992;Thoburn et al 1995;Shier 2001;Thomas 2002) One researcher initially read through the entire set of transcripts noting down initial ideas and developing codes. Then three researchers each coded the same three transcripts to refine the codes.…”
Section: E T H O D Smentioning
confidence: 99%
“…(31) argue that parents' access to reports is especially important as it assists them to prepare their contribution t o t h e conference. As noted, a number of parents in this research did not see reports until just before the conference or until they were actually in the conference room and therefore did not have adequate time to prepare a response to them.…”
Section: Discussionmentioning
confidence: 98%